Financial Aspects of Solving Environmental Problems in a "Green" Growth - ARTEMOVA, Elena; UDOVIK, Elena; SUKHINA, Nadezhda; PETROVSKAYA, Anna; ANICHKINA, Olga; RYABOVA, Taisiya (Journal of Environmental Management and Tourism, 2019)
The article discusses the financial aspects of solving environmental problems in a "green" growth. The possibilities of saving natural resources make it necessary to develop and conduct an effective technological policy in the economy, which in turn should be manifested in the practical implementation of scientific and technological progress in the field of products, technologies and services. A state with environmentally sustainable and balanced economic reforms and creating an economic environment at the macro level can facilitate and accelerate the transition to a green economy. Numerous local, global economic crises of the last decade indicate the instability of the existing world economic structure. The world community continues to discuss the issue of building a new model of the economic system, which is called the "green" economy. Sufficiently strong inflow of investments along with the rapid pace of development of the "green" economy, gave rise to the bold expectations of the prevailing part of politicians and analysts in strong economic growth in the coming decades.